Morphological and Proteomic Analyses to Reveal Salt-Tolerant Mechanisms in Soybean Seedlings Treated with Titanium-Oxide Nanoparticles - Pwint Phoo Wai; Hisateru Yamaguchi; Keisuke Hitachi; Kunihiro Tsuchida; Setsuko Komatsu (Oxygen, 2025)
Because soybean is sensitive to salt stress, it is necessary to improve their stress tolerance. Titanium-oxide nanoparticles (TiO2 NPs) enhanced the growth of soybean under salt stress. To elucidate the promotive effects of TiO2 NPs on soybean growth under salt stress, a gel-free/label-free proteomic analysis was carried out. The principal component analysis of proteins showed that TiO2 NPs affected proteins in roots grown under salt stress. The differentially changed proteins were associated with protein metabolism and transport in the biological process, the nucleus in the cellular component, and nucleic acid binding activity in the molecular function. Proteins identified with proteomics were verified using immunoblot analysis. The abundance of V-ATPase decreased in soybean under salt stress and increased with additional TiO2 NPs under stress, whereas xyloglucan endotransglucosylase/hydrolase did not change with any treatment. The abundance of peroxiredoxin increased under salt stress but decreased with additional TiO2 NPs under stress. These results suggest that TiO2 NPs confer salt tolerance in soybean plants at the early growth stage by regulating vacuole transport and reactive oxygen scavenging systems.